Identification of undiagnosed dementia cases using a web‐based pre‐screening tool: The MOPEAD project. Issue 8 (15th April 2021) - Rodrigo, Adrián; Trigueros, Paloma; Jamilis, Laura; Alegret, Montserrat; Rodríguez, Octavio; Tárraga, Lluís; González‐Pérez, Antonio; Kramberger, Milica; Winblad, Bengt; Visser, Pieter Jelle; Jessen, Frank; Campo, Laura; et al.
Abstract: Introduction: Innovative patient engagement models are required to identify people with prodromal and mild Alzheimer's disease who are "hidden" in their communities and not normally found in a memory clinic setting. Methods: A marketing campaign and a web‐based pre‐screening tool were used to identify individuals at risk of dementia in five European countries. Harmonized clinical evaluation of these patients was performed in participating memory clinics within the MOPEAD project. Results: A total of 1487 individuals completed the pre‐screening, with 547 of them found to be at risk of dementia (36.8%). Among the subset of 91 patients with a positive pre‐screening result that underwent full clinical evaluation, 49 (53.8%) were diagnosed with either mild cognitive impairment or Alzheimer's disease. Conclusion: This novel web‐based pre‐screening tool showed to be a valid strategy to identify undiagnosed people with cognitive impairment.